PENERAPAN KURIKULUM 2013 DALAM MENINGKATKAN KETERAMPILAN, SIKAP, DAN PENGETAHUAN - Otang Kurniaman; Eddy Noviana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
Implementation of the 2013 curriculum is very different from the previous curriculum, there are still many obstacles that we know greatly affect the learning outcomes, both in terms of media used, the assessment in the 2013 curriculum is more complicated than the previous curriculum then the methods used to convey the learning materials that want to be taught not effective or even incompatible with the material to be conveyed. This research method is a classroom action research conducted in improving the learning process, with four meetings. The assessment taken in this study is an evaluation evaluation of each meeting in the form of attitudinal value, value of knowledge and skill value based on teacher's book on theme 4